Suppressed intestinal secondary bile acids in moxifloxacin-induced hyperglycemia: studies in normal and diabetic GK rats - Sun, Yewen; Qu, Yuchen; Yang, Zhuan; Lv, Bo; Wang, Guanjun; Fan, Kai; Wang, Yuyuan; Pan, Jie; Du, Ziyan; Yu, Yunli (Frontiers in Pharmacology, 2025)
ObjectiveMoxifloxacin (MFLX) frequently induces dysglycemia when used in the treatment of infectious diseases, particularly in patients with diabetes. However, the mechanism through which MFLX affects host glucose metabolism remains unclear. This study aimed to investigate the possible mechanism underlying MFLX-induced hyperglycemia.MethodsIn this study, we investigated the short-term (3 days) and long-term (14 days) effects of MFLX on glucose metabolism in normal and type 2 diabetic GK rats. After oral administration of 40 mg/kg of MFLX, blood glucose, insulin, GLP-1, and fibroblast growth factor 15 (FGF15) levels in the blood of rats, as well as bile acids in both blood and feces, and gut microbiota, were examined. Liver and ileum tissues were promptly harvested for detecting the expression of hepatic 7α-hydroxylase (CYP7A1) and intestinal Takeda G-protein-coupled receptor 5 (TGR5) and farnesoid X receptor (FXR). In addition, we explored the effect of secondary bile acids (SBAs) on GLP-1 secretion in NCI-H716 cells, and observed the direct effect of MFLX on the expression of CYP7A1 in HepG2 cells and TGR5, FXR in NCI-H716 cells.ResultsIt was demonstrated that MFLX induced hyperglycemia in diabetic rats, with a more pronounced reduction in serum insulin, GLP-1, and FGF15 levels than observed in normal rats. Gut microbiota associated with SBAs metabolism were significantly reduced, leading to decreased intestinal deoxycholic acid (DCA) and lithocholic acid (LCA). In vitro studies revealed that DCA and LCA (25 μM, 50 μM, and 100 μM) promoted GLP-1 secretion in a concentration-dependent manner in NCI-H716 cells. Meanwhile, we observed that the expression of intestinal TGR5 and FXR significantly downregulated, whereas CYP7A1 expression in liver was increased in GK rats after MFLX treatment. MFLX itself (0.1 μM, 1 μM, and 10 μM) did not directly altered TGR5 or FXR expressions in NCI-H716 cells, nor did it alter CYP7A1 expression in HepG2 cells, which indicated that the impact of MFLX on glucose metabolism was primarily induced by changes in bile acids metabolism resulting from alterations in the gut microbiota.ConclusionOur studies showed MFLX more likely to cause hyperglycemia when used in diabetic states and highlighted the critical role of gut microbiota-SBAs-TGR5/FXR pathway in MFLX-induced hyperglycemia.